(untitled) (Research, Society and Development, 2024)
Introduction: Cystic fibrosis is an autosomal recessive hereditary disease that mainly affects the respiratory system and gastrointestinal tract, and those with this comorbidity may die due to its complications. Objective: This study aims to describe the epidemiological characteristics of deaths from cystic fibrosis in Brazil between 2012 and 2022. Methodology: This is a cross-sectional study, in which the researchers analyzed data available in the Mortality Information System (SIM), of the Department of Information Technology of the Unified Health System (DataSUS). Results: According to the variables investigated, the results found point to the year 2022 with the highest percentage of deaths due to cystic fibrosis with 11.99% (n = 291), a higher prevalence of females, representing 50.87% (n = 1,234), in the age group of 80 years or older, with 16.24% (n = 394), white, with 59.73% (n = 1,449), and the Southeast Region and city of São Paulo, presenting 43.56% (n = 1,057) and 22.63% (n = 549) of total deaths, respectively. Conclusion: Thus, we highlight the importance of encouraging the expansion of health policies for the treatment of individuals with cystic fibrosis, aiming to reduce the number of deaths from this disease in Brazil.